1982
DOI: 10.1007/bf02411251
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effects of aluminum on bone phosphatases: A possible interaction with bPTH and vitamin D3 metabolites

Abstract: Summary. The present study was undertaken to test the in vitro action of aluminum on bone phosphatase activities and the possible interaction of this metal with parathyroid hormone (bPTH) or vitamin D3 dihydroxymetabolites [1,25-and 24,25(OH)2D3). Three-day-old rat calvaria were incubated for 24 h with one of the following: bPTH at 5 • 10-SM, 1,25-or 24,25(OH)2D3 at 2.5 • 10-9M, A1 at concentrations ranging from 3 • 10-11M to 6 • 10-6M, or their corresponding solvents. AI effects were also investigated when th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
1

Year Published

1984
1984
1992
1992

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(15 citation statements)
references
References 12 publications
3
10
1
Order By: Relevance
“…the induction of de novo bone formation with an increase in trabecular bone volume, trabecular number, an increase of the osteoblast number and activ ity producing a large amount of unmineralized woven bone over the whole trabecular surface even in places where resorption had not taken place. The stimulating action of high doses of aluminum and the depressing action of low doses of aluminum in the Quarles' study in the beagle are apparently in contradiction with the in vitro data of Lieberherr et al [46,47] who showed that low doses of aluminum stimulated bone alkaline phospha tase and collagen synthesis whereas the high doses had the opposite effect. A stimulating effect of aluminum on de novo bone formation has also been reported to occur at some times by Galceran et al [48] after relatively low-dose aluminum intoxication in the dog (0.75 mg/kg.…”
Section: Evidences That Aluminum Cannot Be the Sole Culprit In The Pacontrasting
confidence: 53%
See 1 more Smart Citation
“…the induction of de novo bone formation with an increase in trabecular bone volume, trabecular number, an increase of the osteoblast number and activ ity producing a large amount of unmineralized woven bone over the whole trabecular surface even in places where resorption had not taken place. The stimulating action of high doses of aluminum and the depressing action of low doses of aluminum in the Quarles' study in the beagle are apparently in contradiction with the in vitro data of Lieberherr et al [46,47] who showed that low doses of aluminum stimulated bone alkaline phospha tase and collagen synthesis whereas the high doses had the opposite effect. A stimulating effect of aluminum on de novo bone formation has also been reported to occur at some times by Galceran et al [48] after relatively low-dose aluminum intoxication in the dog (0.75 mg/kg.…”
Section: Evidences That Aluminum Cannot Be the Sole Culprit In The Pacontrasting
confidence: 53%
“…In vitro experimental data further support also the direct toxic effect of aluminum on both bone mineralization and on bone formation: not only can Al inhibit hydroxy apatite crystal formation from calcium phosphate in vitro [45] but, at least at high doses, it decreases bone alkaline phosphatase of rat cal varia [46] or of mouse osteoblasts in culture and this is associated with a decreased collagen synthesis and an inhibition of cell proliferation with a decrease of the stimulating effect of PTH on osteoblasts cAMP [47], This decrease of cAMP response to PTH by previous aluminium intoxication was also found in iso lated perfused bone studies [48]. It has recently been explained by a primary effect of aluminum on the affinity of PTH receptor which may be related to exchange of aluminum with magnesium at the G protein level [49].…”
Section: Evidence For the Responsibility Of Aluminum In Adynamic Bonementioning
confidence: 65%
“…Other investigators have reported evidence of an increase in acid and alkaline phosphatase activity in rat calvaria in tissue culture during exposure to low concentrations of aluminum (39). Further study will be required to confirm these observations and to clarify the effect of aluminum on bone resorption in general and on the cellular activity of osteoclasts in particular.…”
Section: Discussionmentioning
confidence: 85%
“…The precise mechanism of this anemia is obscure. Aluminum accumulates in the bone of hemodialysis patients [10][11][12] and it may directly interfere with erythropoiesis. The microcytic features of the anemia suggest a disturbance of normal hemoglobin synthe sis by aluminum.…”
Section: Discussionmentioning
confidence: 99%